ISCHEMIC HEART DISEASE AND ARTERIAL HYPERTENTION AS RISK FACTORS OF SURGICAL TREATMENT OF PATIENTS WITH INFRARENAL SEGMENT OF AORTIC ANEURYSM - N. A. Yaitsky; A. Ya. Bedrov; D. V. Maslevtsov; Ye. A. Tsvetkova; A. A. Moiseev (Вестник хирургии имени И.И. Грекова)
A retrospective analysis of the data of 188 patients with the infrarenal segment of the aortic aneurysm (ISAA) showed, that ischemic heart disease and arterial hypertension were diagnosed practically in all patients — 175 (93.0%) and 177 (94.1%) patients respectively. A decreased retractor function of the myocardium was noted in 88 (46.8%) of patients. According to the findings of echocardiography 134 (71.3%) patients had the arterial hypertension of third degree. For the assessment of the influence of the accompanying cardiac pathology on the results of planned surgical treatment and systematization of postoperative cardiac complications the classification, which was proposed by R. B. Rutherford et al. and modified by A. V. Pokrovsky et al. was used. The obtained data point at a direct proportional relationship between the degree of the initial cardiac status, frequency and severity of postoperative cardiac complications in patients after resection of ISAA in 1.6–2.3 times.